Notes on old and mostly forgotten species of Aphidiidae (Hymenoptera). I. - Mackauer, Manfred (Contributions to Entomology = Beiträge zur Entomologie, 1964)
The paper discusses the taxa of the family Aphidiidae (Hymenoptera) that were described by J.T.C. Ratzeburg. The seven species described by the author were interpreted as follows (original combination included in square brackets): (a) Family Aphidiidae: Praon aphidiiforme (Ratzeburg, 1852), n. comb. [= Bracon a.], = n. syn. of Praon abjectum (Haliday, 1833); Praon aphidivorum (Ratzeburg, 1844), n. comb. [= Aphidius a.], = ? syn. of Praon flavinode sensu auctt., nee Haliday, 1833; Aphidius duodecimarticulatus Ratzeburg, 1852, = n. syn. of Aphidius salicis Haliday, 1834; and Protaphidius wissmannii (Ratzeburg, 1848) Stary, 1958 [= Aphidius w.]. - (b) Family Braconidae, subfamily Alysiinae: Orthostigma flavipes (Ratzeburg, 1844) Ratzeburg, 1848 [= Aphidius f.]; ? Aphaereta flavidens (Ratzeburg, 1844), n. comb. [= Aphidius f.]. - (c) Family Braconidae, subfamily ? Dacnusinae: Gen. inclusus (Ratzeburg, 1852), n.comb. [= Aphidius i.]. Two taxa of the generic level were described by Ratzeburg. They are as follows: Achoristus Ratzeburg, 1852, = n. syn. of Praon Haliday, 1833 (Hymenoptera: Aphidiidae), and Orthostigma Ratzeburg, 1844 (Hymenoptera: Braconidae, Alysiinae). In addition, five species of the family Aphidiidae, that were dealt with by Ratzeburg, were interpreted as to their systematic position.Nomenclatural Actsflavidens (Ratzeburg, 1844) (Aphaereta), comb. n. hitherto Aphidius flavidens Ratzeburg, 1844Achoristus Ratzeburg, 1852 (Aphidiidae), syn. n. of Praon Haliday, 1833duodecimarticulatus Ratzeburg, 1852 (Aphidius), syn. n. of Aphidius salicis Haliday, 1834aphidiiforme (Ratzeburg, 1852) (Praon), comb. n.; syn. n. hitherto Bracon aphidiiformis Ratzeburg, 1852; syn. of Praon abjectum (Haliday, 1833)aphidivorum (Ratzeburg, 1944) (Praon), comb. n. hitherto Aphidius aphidivorus Ratzeburg, 1844